The Impact of Apathetic Disorders on the Quality of Life of Patients after Ischemic Stroke - Jolanta Zielińska; Marek Zieliński; Robert Ślusarz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Strokes often cause dysfunctions in the reception and transmission of speech, which may be aphasia or dysarthria. These disorders can lead to disability, which imposes limitations on the patient, even leads to a complete breakdown of roles and social bonds. Aim. The main aim of the study was to assess the impact of the type and degree of apathetic disorders on the quality of life of patients after ischemic stroke. Material and Methods. The research was carried out at the Neurological Department of the Provincial Specialist Hospital in Włocławek. On average 68 patients with apathetic disorders and diagnosed ischemic stroke were qualified for the study. The study was conducted using the method of diagnostic survey. It consisted in the assessment of patients using the generally available SODA diagnostic tool — the Aphasia Dynamics Assessment Scale and a standardized tool, the WHOQOL-BREF questionnaire by Krystyna Jaracz. Results. When assessing the impact of the degree of aphasia on the quality of life, a statistically significant difference was observed in the overall quality of life in patients with complete (p = 0.012), significant (p = 0.012) and moderate (p = 0.031) aphasia. In self-assessment of health status, a statistically significant difference was found only in patients with complete aphasia (p = 0.048). In the physical, psychological and environmental domains, a statistically significant differences was observed in patients with severe aphasia (p = 0.05). Conclusions. The type and degree of apathetic disorders has been shown to affect the quality of life of patients. Each type of aphasia worsens the overall quality of life, and in addition, motor and sensory aphasia negatively affects functioning in the psychological field. It has also been shown that the more advanced the degree of apathetic disorders, the worse the overall quality of life, self-esteem of health, and worse physical, psychological and environmental functioning. (JNNN 2020;9(3):108–113)